If it's not what You are looking for type in the equation solver your own equation and let us solve it.
Simplifying 8 = -2x + 4 + -2 Reorder the terms: 8 = 4 + -2 + -2x Combine like terms: 4 + -2 = 2 8 = 2 + -2x Solving 8 = 2 + -2x Solving for variable 'x'. Move all terms containing x to the left, all other terms to the right. Add '2x' to each side of the equation. 8 + 2x = 2 + -2x + 2x Combine like terms: -2x + 2x = 0 8 + 2x = 2 + 0 8 + 2x = 2 Add '-8' to each side of the equation. 8 + -8 + 2x = 2 + -8 Combine like terms: 8 + -8 = 0 0 + 2x = 2 + -8 2x = 2 + -8 Combine like terms: 2 + -8 = -6 2x = -6 Divide each side by '2'. x = -3 Simplifying x = -3
| 2x-1=24.5 | | 5+x=5y+5 | | x^2-10x+10= | | 2c/11=c-3/4 | | 6+3x=11-2x | | 256=6x-4(-4x-20) | | 9y+5=5y | | k-76.98=43.56 | | x=9y | | 20x+15-5=180 | | 65+x+x-5=180 | | 3y-9+y+45=5y+40-3y | | 9x+5=5y+5 | | -1=6a-1+6a | | 0.6x-3.9=0.6 | | -8k+26=-8k | | -.5(16-2h)=11 | | 2y+19+y=7y-9 | | 3(x-5)+1=(1/4)(2x-8) | | 11+(7+n)=24 | | -3y+8=-12x | | 4(x-2)/6=2(x+8)/13 | | 2x^2+2x=-74 | | (3/4)(4-x)=3-x | | 4(x-3)+2x=3(2x-5) | | 36x-63=36x+18 | | 3s(2)-5s+9=0 | | 3c(x+2)-5=c(x-3) | | 2=-5n+4n | | 5.5=-2+d | | 4(3q-2)=16 | | x^2-7x+1.25=0 |